2022
DOI: 10.1038/s41598-022-09015-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial symbionts influence host susceptibility to fenitrothion and imidacloprid in the obligate hematophagous bed bug, Cimex hemipterus

Abstract: The use of insecticides remains important in managing pest insects. Over the years, many insects manifested physiological and behavioral modifications resulting in reduced efficacy of insecticides targeted against them. Emerging evidence suggests that bacterial symbionts could modulate susceptibility of host insects against insecticides. Here, we explore the influence of host microbiota in affecting the susceptibility of insect host against different insecticides in the blood-sucking bed bug, Cimex hemipterus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 75 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Insect-infecting Wolbachia strains with major biological effects have been mostly associated with host reproductive disturbances (e.g. CI, parthenogenesis, male-killing and feminization) [43][44][45] and recently with effects on other behavioral and physiological processes, including nutrition, defense and insecticide-resistance [46][47][48][49][50]. In other mirid species, the presence of Wolbachia has been associated with reproductive alterations and nutritional roles.…”
Section: Discussionmentioning
confidence: 99%
“…Insect-infecting Wolbachia strains with major biological effects have been mostly associated with host reproductive disturbances (e.g. CI, parthenogenesis, male-killing and feminization) [43][44][45] and recently with effects on other behavioral and physiological processes, including nutrition, defense and insecticide-resistance [46][47][48][49][50]. In other mirid species, the presence of Wolbachia has been associated with reproductive alterations and nutritional roles.…”
Section: Discussionmentioning
confidence: 99%
“…Insect-infecting Wolbachia strains with major biological effects have been mostly associated with host reproductive disturbances (e.g. CI, parthenogenesis, male-killing and feminization) (Serbus et al 2008;Werren et al 2008;Kaur et al 2021) and recently with effects on other behavioral and physiological processes, including nutrition, defense and insecticideresistance (Hosokawa et al 2010;Nikoh et al 2014;Zug and Hammerstein 2015;Zhang et al 2020;Soh and Veera 2022). In other mirid species, the presence of Wolbachia has been associated with reproductive alterations and nutritional roles.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance mechanisms documented include penetration resistance, metabolic resistance [namely to cytochrome P450 monooxygenases (P450s), esterase, and ATP-binding cassette transporters], and target site insensitivity (kdr) (31,109). Recently, it was found that insecticide susceptibility in C. hemipterus is influenced by the presence of bacterial symbionts (126). Currently, there is no ongoing global monitoring for resistance in bed bugs.…”
Section: Insecticide Resistancementioning
confidence: 99%